Analisis Sumber Daya Manusia, Permodalan Dan Pemasaran Terhadap Kinerja Usaha Kecil Dan Menengah Kripik Apel Di Kecamatan Tutur - Muhammad Fahmul Iltiham (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2018)
This article aims to investigate the influence of Human Resources, Capital And pemasaranTerhadap Small and Medium Enterprise Performance apple chips. And knowing how much influence Human Resources, Marketing Performance Against Capital and the Small and Medium apple chips. The population in this article are the Small and Medium Enterprises chips Apples are in the subdistrict Speech, while samples were used that as many as 20 people consisting of owners of Small and Medium Business Owners apple chips and analyzed using multiple regression analysis. The data used in this article are the primary and secondary data.